Fast Multiple Access Scheme for Satellite Networks Using Control Channels - Lee, Minwoo; Baek, Hoki; Lim, Jaesung (ICTC 2019 - 10th International Conference on ICT Convergence: ICT Convergence Leading the Autonomous Future, 2019)
Nowadays, satellite networks (SATNETs) will serve important role to integrate the terrestrial infrastructures. Since the SATNETs have inherent long time delay, it is needed to reduce the latency to be served properly. Even in a mesh topology, it takes two hops to establish a direct link between two satellite terminals (STs) at initialization. In this paper, we propose a novel multiple access scheme to reduce the time delay, using control channels in SATNETs along with the virtual allocation and the frequency mirroring property. Through numerical analysis, we investigated the expected delay to send a packet among terminals. The results showed that using control channel to make a direct link is feasible for SATNETs.
Keywords: CFDAMA; Control channels; DAMA; Long time delays; Mesh topologies; Multiple access scheme; Satellite network; Satellite terminals; CFDAMA; DAMA; Satellite Networks